de la catastrophe. - Centre d'art contemporain, Genève (Genève : Centre d'Art Contemporain, 1982)
Acconci, Vito ; Chia, Sandro ; Cragg, Tony ; Defraoui, Silvie et Chérif ; Disler, Martin ; General Idea ; Giger, H.R. ; Goldstein, Jack ; Kiefer, Anselm ; Kienholz, Ed ; Middendorf, Helmut ; di Sambuy, Filippo ; Sarkis ; St. Aubsky, Tamach
de la catastrophe, Centre d'Art Contemporain, Genève, Avril - Mai 1982
boek